Dioxin exposure and non-malignant health effects: a mortality study. Issue 2 (February 1998) - Pesatori, A C; Zocchetti, C; Guercilena, S; Consonni, D; Turrini, D; Bertazzi, P A
Abstract : OBJECTIVE: To investigate, in a population heavily exposed to 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin (TCDD), the possible unusual occurrence of diseases other than cancer. METHODS: Five year extension of the follow up of the cohort involved in the Seveso accident. Soil measurements identified three exposure zones: (A) highest contamination, (B) substantial, and (R) low but higher than background contamination. Blood TCDD measurements, although limited in number, confirmed zone exposure ranking. The 15 year mortality in the exposed cohort was compared with that of a large population in the surrounding non-contaminated territory. Relative risks (RRs) and 95% confidence intervals (95% CIs) were estimated with Poisson regression techniques. RESULTS: The already noted increased occurrence of cardiovascular deaths was confirmed, in particular in zone A, among males for chronic ischaemic heart disease (five deaths, RR 3.0, 95% CI 1.2 to 7.3), and among females for hypertensive disease (three deaths, RR 3.6, 95% CI 1.2 to 11.4) and chronic rheumatic heart disease. Novel findings were the increase of chronic obstructive pulmonary disease, most notably among males in zone A (four deaths, RR 3.7, 95% CI 1.4 to 9.9) and females in zone B (seven deaths, RR 2.4, 95% CI 1.1 to 5.1); and from diabetes, which was significantly increased in females in zone B (13 deaths, RR 1.9, 95% CI 1.1 to 3.2). In zone R, chronic ischaemic heart disease (males and females), hypertension (females), and diabetes (females) showed less pronounced, although significant excesses. CONCLUSIONS: As well as high TCDD exposure, the accident caused a severe burden of strain in the population. Both these factors might have contributed to the noted increased risks (in particular, circulatory and respiratory). The cardiovascular and immune toxicity of TCDD, as well as its complex interaction with the endocrine system, might be relevant to the explanations of these findings. These results, although not conclusive, concur with previous data in suggesting cardiopulmonary and endocrine effects in humans highly exposed to TCDD.